Maternal exercise intervention in obese pregnancy improves the cardiovascular health of the adult male offspring - Jessica H. Beeson; Heather L. Blackmore; Sarah K. Carr; Laura Dearden; Daniella E. Duque-Guimarães; Laura C. Kusinski; Lucas C. Pantaleão; Adele G. Pinnock; Catherine E. Aiken; Dino A. Giussani; Denise S. Fernandez-Twinn; Susan E. Ozanne (Elsevier, 2018)
Objective: Obesity during pregnancy is associated with an elevated risk of cardiovascular disease in the offspring. With increased numbers of women entering pregnancy overweight or obese, there is a requirement for targeted interventions to reduce disease risk in future generations. Using an established murine model of maternal obesity during pregnancy, we investigated if a treadmill exercise intervention in the mother could improve offspring cardiac health and explored potential underlying mechanisms. Methods: A 20-minute treadmill exercise intervention protocol was performed 5 days a week in diet-induced obese female C57BL/6 mice 1 week prior to, and up to E17 of pregnancy. All male offspring were weaned onto a control diet and studied at 8 weeks of age when their cardiovascular physiology was assessed by in vivo echocardiography and non-invasive tail cuff plethysmography. Cardiomyocyte cell area, re-expression of fetal genes and the expression of calcium handling and sympathetic activation proteins were determined. Results: At 8 weeks, there was no difference in bodyweight or fat mass between groups. Offspring of obese dams developed pathologic cardiac hypertrophy, hypertension and cardiac dysfunction characterized by reduced ejection fraction (p < 0.001). Maternal exercise prevented cardiac hypertrophy and dysfunction but failed to prevent hypertension. These offspring of exercised dams also had enhanced (p < 0.001) levels of calcium handling proteins and a sympathetic-activated inotropic response. Conclusions: Exercise in obese pregnancy was beneficial to offspring cardiac function and structure but did not influence hypertension suggesting they are programmed by separate mechanistic pathways. These data suggest combination interventions in obese pregnancies will be required to improve all aspects of the cardiovascular health of the next generation. Keywords: Pregnancy, Obesity, Exercise, Hypertrophy, Echocardiography